Management of financing and development of the micro and small manufacturing company in the departament of Huánuco - Palomino-Gonzales, Julia (2020)
The objective of this research was to demonstrate that financing management influences the development of manufacturing micro and small companies (MYPE) in the Huánuco region in 2017. It was a research with a quantitative, applied, analytical, and longitudinal and design focus quasi-experimental. The population was 1,722 MYPES, and 50 of them were selected by non-probalistic sampling at the researcher's convenience. In the data collection, an interview of general characteristics and a questionnaire of knowledge of the management of financing and business development, validated and with 0.8 reliability were used. Ethical considerations for research were applied. The results show that the variables: need for financing, choice of financial provider, management of disbursements and access to credit in the pre-test were rarely considered in the frequency; in the post test there were changes towards the frequency of always or sometimes. The development of the MYPE in the pre-test was evaluated as moderate by 44% of the experimental group. In the control group, 72% considered it to be minimal. In the post test, in most of the experimental group, the moderate level of development predominated (80.0%) and 12% of the control group, reached the moderate level. According to the t-Student test, t = 24,699, p 0.000 was obtained, with significant mean differences, observing greater development in the experimental group and concluding that the application of financing management develops manufacturing MYPE, for which reason it is considered feasible application.